2022
DOI: 10.1088/1361-6587/ac44e5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of charging of dust grains in the presence of energetic electrons

Abstract: The role of hot electrons in the charging of dust grains is investigated in a two-temperature hydrogen plasma. A variety of dust particles are introduced into the system and secondary electron emission (SEE) from each of the dust grains has been reported. A cylindrical Langmuir probe is used for determining the plasma parameters and a Faraday cup is connected to an electrometer in order to measure the dust current. The electrometer readings confirm the electron emission from the dust and SEE is observed from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…5. It shows that in the presence of dust grains, there is a significant rise in the density of the cold component of electrons in a two-electron temperature plasma due to the secondary electron emissions from the dust, caused by the electron group with higher temperature [28,40]. Besides this, the electron temperature does not change significantly.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…5. It shows that in the presence of dust grains, there is a significant rise in the density of the cold component of electrons in a two-electron temperature plasma due to the secondary electron emissions from the dust, caused by the electron group with higher temperature [28,40]. Besides this, the electron temperature does not change significantly.…”
Section: Resultsmentioning
confidence: 92%
“…For those plasmas containing hot electrons as the dominant group, the IAWs acts as a suitable diagnostic tool to determine the presence of cold electrons [15]. Moreover, dust charging study in a two-electron temperature plasma has revealed secondary electron emissions (SEE) from Tungsten (W) dust grains [28]. The study shows that the SEE from the dust grains results in an increase in the density of cold electrons, which is expected to have a significant effect on the propagation of IAWs.…”
Section: Introductionmentioning
confidence: 99%
“…The field also guides the primary electrons from the filaments towards the junction of the two cages. Therefore, the total electron flux increases significantly at the centre, and consequently, the probability of interaction of these energetic electrons with the dust grains increases, which leads to a sufficient number of secondary electrons emitted from the dust grains (Paul et al 2022).…”
Section: Variation Of Phase Velocity Of Iawsmentioning
confidence: 99%
“…For those plasmas containing hot electrons as the dominant group, the IAWs acts as a suitable diagnostic tool to determine the presence of cold electrons (Jones et al 1975). Moreover, dust charging study in a two-electron temperature plasma has revealed secondary electron emissions (SEE) from tungsten dust grains (Paul et al 2022). The study shows that the SEE from the dust grains results in an increase in the density of cold electrons, which is expected to have a significant effect on the propagation of IAWs.…”
Section: Introductionmentioning
confidence: 99%
“…However, their presence has a profound effect on the plasma dynamics. [7,8] In the edge region of the fusion devices, the energetic electrons are often generated by lower hybrid resonance or electron cyclotron heating. These electrons have a considerable impact on the energy transport to the plasma-facing wall.…”
Section: Introductionmentioning
confidence: 99%